Label-free versus conventional cellular assays: Functional investigations on the human histamine H1 receptor. (December 2016) - Lieb, S.; Littmann, T.; Plank, N.; Felixberger, J.; Tanaka, M.; Schäfer, T.; Krief, S.; Elz, S.; Friedland, K.; Bernhardt, G.; Wegener, J.; Ozawa, T.; et al.
Graphical abstract: Abstract: A set of histamine H1 receptor (H1 R) agonists and antagonists was characterized in functional assays, using dynamic mass redistribution (DMR), electric cell-substrate impedance sensing (ECIS) and various signaling pathway specific readouts (Fura-2 and aequorin calcium assays, arrestin recruitment (luciferase fragment complementation) assay, luciferase gene reporter assay). Data were gained from genetically engineered HEK293T cells and compared with reference data from GTPase assays and radioligand binding. Histamine and the other H1 R agonists gave different assay-related pEC50 values, however, the order of potency was maintained. In the luciferase fragment complementation assay, the H1 R preferred β-arrestin2 over β-arrestin1. The calcium and the impedimetric assay depended on Gq coupling of the H1 R, as demonstrated by complete inhibition of the histamine-induced signals in the presence of the Gq inhibitor FR900359 (UBO-QIC). Whereas partial inhibition by FR900359 was observed in DMR and the gene reporter assay, pertussis toxin substantially decreased the response in DMR, but increased the luciferase signal, reflecting the contribution of both, Gq and Gi, to signaling in these assays. For antagonists, the results from DMR were essentially compatible with those from conventional readouts, whereas the impedance-based data revealed a trend towards higher pKb values. ECIS and calcium assays apparently only reflect Gq signaling, whereas DMR and gene reporter assays appear to integrate both, Gq and Gi mediated signaling. The results confirm the value of the label-free methods, DMR and ECIS, for the characterization of H1 R ligands. Both noninvasive techniques are complementary to each other, but cannot fully replace reductionist signaling pathway focused assays.